2017
DOI: 10.3748/wjg.v23.i15.2673
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of fibrinogen-like protein 2 protects against T cell-induced colitis

Abstract: AIMTo determine the effect of overexpression of fibrinogen-like protein 2 (FGL2) on regulatory T cell (Treg) and effector T (Teff) cell function on T cell-induced colitis in Rag1-/- mice.METHODSTreg and Teff cells from fgl2-/-, fgl2+/+, and fgl2Tg mice were purified by FACS. They were studied in vitro for immunosuppressive activity and cell proliferation and in vivo for their effects on the development and prevention of T cell-induced colitis in Rag1-/- mice.RESULTSIn vitro, fgl2Tg Treg had enhanced immunosupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Soluble FGL2 (sFGL2) is an immunosuppressive factor that inhibits dendritic cells (DCs) [10] by binding to the FcγRIIB receptor [11]. As an immune regulator, sFGL2 plays a critical role in the immune balance in autoimmune diseases and can restrict the progression of autoimmune glomerulonephritis [12] and T cell-induced colitis [13]. However, in viral hepatitis, sFGL2 attenuates antiviral immunity, leading to poor prognosis, with impaired Treg function and prolonged survival time observed following FGL2 blockage in murine models of viral fulminant hepatitis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble FGL2 (sFGL2) is an immunosuppressive factor that inhibits dendritic cells (DCs) [10] by binding to the FcγRIIB receptor [11]. As an immune regulator, sFGL2 plays a critical role in the immune balance in autoimmune diseases and can restrict the progression of autoimmune glomerulonephritis [12] and T cell-induced colitis [13]. However, in viral hepatitis, sFGL2 attenuates antiviral immunity, leading to poor prognosis, with impaired Treg function and prolonged survival time observed following FGL2 blockage in murine models of viral fulminant hepatitis [14].…”
Section: Introductionmentioning
confidence: 99%
“…To date, experimental evidence is still lacking to address which cell type drives Fgl2 expression in intestinal inflammation, we found that colonic macrophages are the major source of both mFgl2 and sFgl2 in colitis. A recent report implied that Tregs and effector T cells control intestinal homeostasis through expression of Fgl2 in a T cell-induced colitis model ( 29 ). Similarly, we propose here that in the context of inflammation, colonic macrophages may through express Fgl2 partially restore intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have reported that Treg cells are a major source of FGL2, other cells including macrophages and CD8 + T cells can produce FGL2. Hence at this time we cannot unequivocally state that increased FGL2 in the plasma is solely due to production by Treg . We used mice that were genetically deficient in fgl2 to study the effects of FGL2 on both the innate and adaptive antiviral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Hence at this time we cannot unequivocally state that increased FGL2 in the plasma is solely due to production by Treg. 22,51,52 We used mice that were genetically deficient in fgl2 to study the effects of FGL2 on both the innate and adaptive antiviral immune response. Post LCMV cl-13 infection, fgl2 À/À mice had increased numbers of macrophages and DC that expressed CD80, CD86 and MHC-II, markers of macrophage and DC activation in comparison with fgl2 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%